2008
DOI: 10.1021/ic801870w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Cationic Donor-Stabilized Phosphenium Adducts and Their Unexpected P-Substituent Exchange Reactions

Abstract: The reaction between two 1,3-dialkylimidazolium-2-carboxylates 1a and 1b and two different dichlorophosphines (RPCl(2), with R = Ph and NEt(2)) led to new donor-stabilized phosphenium adducts. When the reaction was performed with the 1,3-dimethylimidazolium-2-carboxylate 1a and PhPCl(2) in a 2:1 ratio, the phosphine 4a, bearing two imidazolium moieties, was obtained and led to 5a, after an anion exchange reaction with KPF(6), the latter being fully characterized by an X-ray structure analysis. In similar condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 21 publications
(26 reference statements)
2
46
0
Order By: Relevance
“…The formation of the phosphorus-carbon bond between the N-heterocycle and the phosphorus atom was confirmed by the presence of a doublet at 141.39 ppm in the 13 C NMR spectrum, with a typical coupling constant 1 J P,C of 47 Hz. [10,11] This observation, combined with a 2:1 ratio for furyl versus imidazolium groups in its proton NMR spectrum, unambiguously proved the formation of the expected ligand 3d.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The formation of the phosphorus-carbon bond between the N-heterocycle and the phosphorus atom was confirmed by the presence of a doublet at 141.39 ppm in the 13 C NMR spectrum, with a typical coupling constant 1 J P,C of 47 Hz. [10,11] This observation, combined with a 2:1 ratio for furyl versus imidazolium groups in its proton NMR spectrum, unambiguously proved the formation of the expected ligand 3d.…”
Section: Resultsmentioning
confidence: 66%
“…[10] Besides, this synthesis provides access to new dicationic or mixed halide donor-stabilized phosphenium adducts by extension of the reactivity of 1 towards others chlorophosphines. [11] Moreover, the measurement of the A 1 symmetric stretching frequency of the related Ni(CO) 3 A C H T U N G T R E N N U N G (3a-c) complexes has shown that the ligands 2 and 3 behave as phosphite-like strong p-acceptors. This unexpected result is the consequence of the C!P bond in imidazolium-2-phosphines which displaces the formal positive charge from the imidazolium ring to the phosphorus center.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In the P-Ph series, the P-coordinating limit towards a Rh(I) center was shown to be reached for the imidazolo-imidazoliophosphine (mono-N-methylated analogue of A Ph ), competitive Ncoordination being also observed, the dicationic diimidazoliophosphine B Ph being non coordinating at all. 17,12 Considering a promoted oxygen atom as a Lewis acid, 18 the corresponding P-oxides C R , D R can be considered as non-metallic P-coordination complexes. 12b In this case, the P-substituent R was demonstrated to have a critical influence on the oxidation potential of dications B R :…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this observation and of the recent calculations on donor P-acceptor systems [5], ligands 2 and 3 will be drawn as donor stabilized-phosphenium structure instead of classical imidazolium-2-phosphines. Moreover, this electronic property combined with their hydrophilic character, which strongly depends on the imidazol-2-ylidène number and nature or counter-anion nature [7], renders such ligands very promising for the development of A mixture of imidazolium-2-phosphine hexafluorophosphate (0.246 g, 0.58 mmol) (prepared according to the literature [6]) and [RhCl(1,5-COD)] 2 (0.142 g, 0.29 mmol) (commercial compound from Strem) in CH 2 Cl 2 (7 mL) were stirred at room temperature for 3 h. The solvent was then removed under vacuum to afford a yellow solid (0.383 g, 99%). 1 Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, among these cationic ligands, the imidazolium-2-phosphines are furthermore very interesting in basic research, because they represent rare examples of base-donor P-acceptor adducts involving an electron rich P III -center as Lewis acceptor [5]. We have thus focused our interest on such ligands, with special emphasis on the development of short and/or easy synthetic methods and recently found a straightforward synthesis of imidazolium-2-phosphines 2a-c and 3 based on the direct addition of chlorophosphines [6,7] to the 1,3-dimethylimidazolium-2-carboxylate 1, see Scheme 1.On the other hand, our preliminary IR studies performed by the measurement of mCO carbonyl absorption band in the related Ni (CO) 3 (2a-c) complexes have shown an unexpected weak basicity of ligands 2 comparable to phosphites. This result could be the consequence of the nature of the C ?…”
mentioning
confidence: 99%